Walk on the wild side - Oldland, Nicholas (Oldland, Nicholas. Life in the wild., 2015)
One day, the three friends, a bear, a moose and a beaver, who loved adventure set off to climb a mountain together. But on the way there, they decide to make it more exciting by turning the climb into a race to the top. It's only after being sidelined by a series of mishaps -- a boulder tumbling down the path, the moose hanging off the side of the cliff, the bear hanging off the moose hanging off the side of the cliff -- that the three friends realize competitions don't always make for a good time.